2018
DOI: 10.23969/biosfer.v3i1.1199
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh BAP Dan NAA Terhadap Waktu Pertumbuhan Tanaman Kantong Semar(Nepenthes adrianii) Secara In-Vitro

Abstract: Nepenthes adrianii (Kantong Semar) merupakan tanaman endemik khas Gunung Slamet, termasuk da-lam Convention on International Trade of Endangered Species(CITES).Salahsatu potensi Nepenthes adrianii sebagai pengendali se-rangga dan tanaman obat. Penelitian ini bertujuan untuk: 1)menentukan konsentrasi interaksi BAP dan NAA yang paling baik dan waktu munculnya untuktunas, akar dan daun. Metode yang digunakan adalah metode eksperimental.Tahap munculnya tunas, akar dan daunmenggunakan Rancangan Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Shoots appear when the ratio between cytokinin hormone is higher than auxin hormone so that the cell does cell division continuously and differentiates towards the formation of shoots Enni Suwarsi Rahayu & Nabila Cyntia Banowati / Biosaintifika 14 (3) (2022): 417-421 (Urry et al, 2017). Nuryadin (2018) reported that the time of shoot initiation was not influenced by the interaction of the BAP hormone with NAA but from the BAP hormone independently. The number of shoots was influenced by BAP concentration, sucrose concentration, and their interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Shoots appear when the ratio between cytokinin hormone is higher than auxin hormone so that the cell does cell division continuously and differentiates towards the formation of shoots Enni Suwarsi Rahayu & Nabila Cyntia Banowati / Biosaintifika 14 (3) (2022): 417-421 (Urry et al, 2017). Nuryadin (2018) reported that the time of shoot initiation was not influenced by the interaction of the BAP hormone with NAA but from the BAP hormone independently. The number of shoots was influenced by BAP concentration, sucrose concentration, and their interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Nepenthes can be propagated conventionally using seeds and stem cuttings or nonconventional propagation using tissue culture techniques (Devi et al, 2013;Dinarti et al, 2010;Rosmaina and Aryani, 2015;Sukamto, 2011;Nuryadin, 2018). However, Nepenthes is a dioecious plant whose insect such as Diptera and Hymenoptera assists the pollination, or sometimes aided by the wind, and many pitchers have offspring from crosses of several species and the resulting impurity seed (Cheek and Jebb, 2001).…”
Section: Nepenthes Reinwardtiana Miq) Through Callus Inductionmentioning
confidence: 99%